2010
DOI: 10.1093/rheumatology/keq300
|View full text |Cite
|
Sign up to set email alerts
|

How well do patient reports reflect adverse drug reactions reported by rheumatologists? Agreement of physician- and patient-reported adverse events in patients with rheumatoid arthritis observed in the German biologics register

Abstract: Patient reports on ADRs are a useful source of information on the safety of new therapies. However, drug surveillance cannot rely on patient reports only, since even life-threatening events were not reported as ADRs by the patients who failed to associate them with the therapy. When coding patient reports on ADRs to a standard coding system, the differences in language and terminology between patients and physicians should be taken into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
19
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 17 publications
4
19
0
4
Order By: Relevance
“…The total Cohen's kappa value was 0.15, which represents slight agreement, and was similar to our results. For rheumatoid arthritis, the reporting of adverse drug events between patients (n = 4246) and physicians differed; even for serious adverse events, the agreement was only 37% [58], whereas patients reported more events, which is similar to our results. In a study comparing adverse events reported in postdischarge patient interviews with adverse events detected by medical record review, the agreement for adverse events (kappa = 0.20) and serious adverse events (kappa = 0.33) was low and comparable to our agreement results [59].…”
Section: Discussionsupporting
confidence: 88%
“…The total Cohen's kappa value was 0.15, which represents slight agreement, and was similar to our results. For rheumatoid arthritis, the reporting of adverse drug events between patients (n = 4246) and physicians differed; even for serious adverse events, the agreement was only 37% [58], whereas patients reported more events, which is similar to our results. In a study comparing adverse events reported in postdischarge patient interviews with adverse events detected by medical record review, the agreement for adverse events (kappa = 0.20) and serious adverse events (kappa = 0.33) was low and comparable to our agreement results [59].…”
Section: Discussionsupporting
confidence: 88%
“…It has, however, been shown that healthcare professionals downgrade the severity of ADEs experienced by patients [ 4 ]. Additionally, it has been shown that healthcare professionals underestimate symptomatic, subjective ADEs [ 4 - 7 ]. In a literature review, it was for instance shown that ADE rates of constipation with the use of the glucose-lowering drug metformin ranged from 0.6-1.0% when reported by healthcare professionals, and was 21% when reported by patients [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…This acknowledgement is especially the case for many symptomatic ADEs for which there is no objective test. Assessment of such ADEs is important, since they influence a patient’s quality of life (QOL) [ 7 ]. Previous studies showed that an increase in total scores of the number, frequency, and severity of experienced ADEs is associated with a decrease in QOL [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…This may result from clinicians not asking the right questions or not listening to patients’ answers, but there are also reasons to believe that patients sometimes feel inhibited discussing symptoms with doctors. Whatever the cause, it is surely not good medicine when we find that, for instance, the rate of appetite loss reported by cancer patients is six times higher than the rate documented in case notes [1], or where drug-related toxicities are reported at a 50% higher incidence by rheumatology patients than their doctors [2]. …”
mentioning
confidence: 99%